PENGARUH CUSTOMER RATING PADA MINUMAN KOPI TERHADAP KEPUTUSAN PEMBELIAN DI KOTA BATAM - Rosie Oktavia Puspita Rini; Tirta Mulyadi; Miratia Afriani; Mohammad Thandzir (Puslitabmas Batam Tourism Polytecnic, 2022)
This study aims to determine how much influence the customer rating has on the decision to purchase coffee drinks in Batam City. Where more and more business people are facilitated by online applications to further increase sales. The independent variable is customer rating and the dependent variable is purchasing decisions. The research method used is quantitative method with the type of research used is descriptive verification, with a sample of 110 respondents. The sampling technique used in this research is non-probability sampling, with purposive sampling as a derivative. The data analysis method used in this research is descriptive analysis method, and simple linear regression analysis. Data processing is done using SPSS software. Through the R test, the customer rating has a strong influence on purchasing decisions. The influence of customer rating on purchasing decisions is 22.6% and the remaining 77.4% is influenced by other factors not examined. Each increase of one customer rating scale will increase the purchase decision by 0.476. Partially seen from the t test, there is an influence of customer rating on the decision to purchase coffee drinks in Batam City.